Toxicology of Ixodes ricinus, the European tick - Bonnet, M.S. (British Homeopathic Journal, 1998)
The following paper is a summary of studies of Ixodes ricinus, the European castor bean tick, and its toxicology. A materia medica based on human envenomation by I. ricinus is also provided.
Keywords: Arachnida; Ixodes ricinus; Ticks; Toxicology